IMPROVING ENGLISH VOCABULARY THROUGH PEER LEARNING ACTIVITIES - Azzahra, Fatimah; Muliati, A.; Aeni, Nur (Universitas Negeri Makassar, 2025)
This quantitative study aims to explore the effectiveness of peer learning activities in improving students’ English vocabulary. The research employed a pre-experimental design involving one group pretest-posttest, with participants consisting of 25 eighth-grade students at SMP Negeri 1 Parangloe. Data were collected through vocabulary tests administered before and after the peer learning intervention. The findings indicate a notable improvement in students’ vocabulary mastery. Pretest results showed that 68% of students were in the